Sustaining forest in Peninsular Malaysia: existing forest laws and Malaysia's international commitments / Adzidah Yaakob - Yaakob, Adzidah (2014)
This paper seeks to address and discuss the importance of related national and international law in ensuring the sustainability of forest particularly in Peninsular Malaysia. The international commitments here refer to Multilateral Environmental Agreements which are related to forests and forestry and to which Malaysia is a party. The Malaysian Forest Law refers to forests Acts and Policies, inter alia the National Forestry Policy 1978 (Revised 1992) (the NFP) and the National Forestry Act 1984 (The NFA); other related government policies on forest conservation are referred to wherever relevant. Besides the challenges in compromising forest for the sake of economy, public rights upon forest is also another challenge to deal with. It is essential to look at related legislation on forest in order to perceive the sustainability of forest in Peninsular Malaysia.